Family resilience is a protective buffer in the relationship between infertility-related stress and psychological distress among females preparing for their first in vitro fertilization–embryo transfer. Issue 4 (21st April 2022) - Kang, Xiaofei; Fang, Mei; Li, Guopeng; Huang, Yuzhen; Li, Yuli; Li, Ping; Wang, Hongmei
ABSTRACT: The present study aimed to evaluate psychological distress and scrutinized whether family resilience plays a moderating role in the association between infertility-related stress and psychological distress among infertile females preparing for their first IVF-ET. A total of 492 infertile females completed self-reported measures including the Kessler 10 Psychological Distress Scale (K10), the fertility problem inventory (FPI), and the Family Resilience Assessment Scale (FRAS). The results showed 21 (65.2%) participants reported moderate or higher levels of psychological distress. While controlling for economic status, we found psychological distress to be positively linked to infertility-related stress ( β =0.483,   P< 0.001), and negatively related to family resilience ( β =-0.145,   P =0.001). The simple slopes analysis showed that infertility-related stress had a weaker positive association with psychological distress for individuals at 1 SD ( β  = 0.443,   P  < 0.001) above the mean on family resilience compared to those at 1 SD ( β  = 0.537,   P  < 0.001) below the mean. Thus, it suggests that clinical practice should conduct family resilience–oriented interventions to facilitate family resilience among infertile females preparing for their first IVF-ET, with the goal to reduce psychological distress.